A project manager’s important professional skills (Journal of Economic Research & Business Administration, 2016)
Kazakhstani companies face international competition and necessity to manage projects with success. The project is successful if effectively managed. A project manager is in charge of all the aspects of the project and responsible for achieving goals and objectives of any project. To perform successfully a project manager has to communicate effectively with a wide variety of stakeholders. From this point of view so-called "soft skills" are more important that "hard" ones because a project manager's authority may be frustrated by siloing effects. A project manager needs two kinds of skills: the management-related skills (hard) and interpersonal ones (soft). To lead a project to success, a project manager must be able to use interpersonal skills with ease. People are the central part of project management, not the procedures and techniques. Procedures and techniques are merely tools that help people make their projects successful. Soft skills deal with human factor issues and, until recently, have been less discussed in project management literature.
Keywords: project; project management; project manager; soft and hard skills; siloing effects; EQ (emotional quotient); stakeholders; interpersonal skills.